2021
DOI: 10.2147/amep.s327739
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Medical, Pharmacy, and Nursing Students Towards Pharmacovigilance and Adverse Drug Reaction Reporting at University of Gondar College of Medicine and Health Sciences, Northwest Ethiopia: A Cross-Sectional Study

Abstract: Background The adequate knowledge, attitude, and practice (KAP) of pharmacovigilance and ADRs reporting is crucial for health care students. Objective This study aimed at assessing the KAP of final-year medical, pharmacy, and nursing (MPN) students towards pharmacovigilance and ADRs reporting at the University of Gondar, College of Medicine and Health Sciences, Northwest Ethiopia. Methods A cross-sectional study was conducted among 296 final-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Additionally, comparable findings were found in other regions of Ethiopia, where nurses ( P =0.001) and health officers ( P =0.019) had less knowledge than pharmacists [ 19 ]. A study conducted at the University of Gondar in Ethiopia found that nursing students had a higher mean rank attitude score than that of pharmacy students and medical students ( P =0.017) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, comparable findings were found in other regions of Ethiopia, where nurses ( P =0.001) and health officers ( P =0.019) had less knowledge than pharmacists [ 19 ]. A study conducted at the University of Gondar in Ethiopia found that nursing students had a higher mean rank attitude score than that of pharmacy students and medical students ( P =0.017) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of Farcas [9], 75.4% strongly agreed that pharmacovigilance should be taught to all healthcare students during the course. Similarly, the study by Tekel et al [13] showed that 49.0% strongly agreed that pharmacovigilance should be taught in the curriculum of all healthcare students. A study by Sivadasan [12] showed that 35.7% strongly agreed that pharmacists were among the most important healthcare professionals reporting ADRs.…”
Section: Discussionmentioning
confidence: 91%
“…9,10,17 The 77.2% doctors opine that a single ADE is significant on the database and as such, majority of them view ADE reporting as a professional obligation. [16][17][18][19] The attitude of 14.9% doctors who do not have a positive response to ADE reporting needs to be changed. Also, 9.9% doctors feel that ADE from OTC, herbal/ nonallopathic drugs need not be reported.…”
Section: Discussionmentioning
confidence: 99%
“…The 70.3% doctors observe ADE with polypharmacy, 57.4% doctors with skin, paediatric and elderly patients and 40.6% doctors with food and drinks. [16][17][18][19] The 10,13,17-,23 On testing the association between the responses of doctors having received training on ADE reporting and their response on the maximum ADE being due to polypharmacy, they are found to be statistically significant. (p<0.05).…”
Section: Discussionmentioning
confidence: 99%